The Merchant Income This study discusses the factors that influence merchant income during the Covid 19 pandemic in Surabaya in 2020: Faktor-Faktor Yang Mempengaruhi Pendapatan Pedagang Saat Pandemi Covid-19 di Kota Surabaya Tahun 2020 (Studi Kasus di Pasar Pucang Surabaya ) - Budi Prayitno; Renta Renta (Media Mahardhika, 2021)
Since the Covid-19 pandemic that hit the Surabaya City certainly affects the economic changes in the Surabaya City. Clearly seen from the purchasing power parity and merchant income and salary and working hour. This impact to sale and purchase of goods and service causes changes in merchant income. This study discusses the factors that influence merchant income during the Covid 19 pandemic in Surabaya in 2020. This purpose of the study is to look at the capabilities and changes in the economy from the producer side. This study took location in Surabaya Pucang Market, with concern from the merchant income, so using multiple linier regression and Cross Section data. The independent variables in the study are output selled, salary and working hour have a positive and significant effect partially and simultaneously on dependent variable is merchant income in the Pucang Market Surabaya on 2020. Keywords: merchant income, output selled, salary, working hour.